Efficiency and Choquet boundaries in separated locally convex spaces - Vasile Postolică (International Journal of Mathematics and Mathematical Sciences)
This research paper is devoted to the study of the properties for Pareto-type efficient point sets in separated locally convex spaces, based upon an earlier result on the coincidence of Pareto-type efficient point sets and the Choquet boundaries and the natural corresponding extension for the approximate efficient point sets in Hausdorff locally convex spaces. Both of these results represent an important connection between two great fields of mathematics: vector optimization and potential theory.